Informed Consent through Community Engagement in Collaborative Research in Developing Countries - Nurunnabi, Abu Sadat Mohammad; Sony, Sadia Akther; Begum, Munira; Sharmin, Saida; Haseen, Fariha; Baset, Md Kamran Ul (Community Based Medical Journal, 2023)
Multinational nature of research activities has been growing increasingly through collaboration that involves a developing country and a developed country. However, several scandals have been reported to date in such research done by the western authorities in the name of collaboration, development, or health improvement in different developing countries especially revolving informed consent and protection of the participants. Those incidences tend to create distrust and may result in non-cooperative attitude among developing countries in further collaboration. This paper aims to discuss how much an informed consent is really informed and how community engagement can make it more meaningful and ethical by respecting the values of any society (i.e., participating developing country). Evidence suggests that there are essential interdependence and overlapping between consenting process and community engagement in that collaborative research. Community engagement is able to provide a meaningful insight that helps in formulation of context-specific consent process. It also helps to regulate and monitor consenting procedure, withdrawal from participation, and any relevant changes while research is ongoing. Moreover, as a sign of showing respect to the participating group in research, community engagement has been found instrumental in making research more acceptable and mutually beneficial. CBMJ 2023 July: Vol. 12 No. 02 P: 192-200